Analisis Live Streaming Dan Advertisement Terhadap Minat Beli Konsumen Produk SkincareThe Originote Pada Aplikasi Tiktok (Survei Pada Gen Z Kota Sukabumi) - Revinaldi, Revinaldi; Komariah, Kokom; Saori, Sopyan (JURNAL MANAJEMEN MOTIVASI, 2025)
The growth of digital technology has led to the emergence of platforms such as TikTok Shop. Consumer purchase intention is a key factor in business sustainability, making it important for companies to understand the market, promote their products, and predict consumer behavior. The purpose of this study is to determine the effect of live streaming on purchase intention and to examine the effect of advertisement on purchase intention. This research uses a descriptive quantitative approach with a multiple linear regression model, and sampling was conducted using purposive sampling among the Gen Z population in Sukabumi City. The results of this study show that live streaming has a positive and significant effect on purchase intention. Likewise, advertisement also has a positive and significant effect on purchase intention.